Simultaneous anaerobic and aerobic transformations of nitrobenzene. (15th November 2018) - Cao, Lifeng; Zhang, Chenyuan; Zou, Shasha; Zhu, Ge; Li, Naiyu; Zhang, Yongming; Rittmann, Bruce E.
Abstract: Aerobic biodegradation of nitrobenzene (NB) produces nitrophenol (NP), which has stronger toxicity than NB. Anaerobic biodegradation of NB produces aniline (AN), which has weaker toxicity, but is a dead-end product in anaerobic conditions. Accumulation of AN should be overcome by coupling anaerobic and aerobic transformations: NB is transformed to AN in an anaerobic zone of the bioreactor, and AN is then transformed in an aerobic zone. A vertical baffled bioreactor (VBBR) was employed for NB biodegradation with a controlled dissolved oxygen (DO) concentration. NB biodegradation was accelerated by simultaneous anaerobic and aerobic transformations, since AN was biotransformed by a mono-oxygenase reaction. Adding exogenous electron donor (acetate) enhanced NB removals when the DO concentration was ∼0.5 mg/L, because the donor accelerated mono-oxygenations of NB and AN. Coupling anaerobic and aerobic transformations can be a valuable strategy for biodegrading organic compounds that undergo aerobic and anaerobic biotransformations. Graphical abstract: Image 1 Highlights: Anaerobic transformation of nitrobenzene (NB) produced aniline (AN). AN was a dead-end product in anaerobic conditions. Aerobic transformation of AN allowed its mineralization. Simultaneous aerobic and anaerobic conditions accelerated NB biodegradation. Extra election donors accelerated NB and AN biodegradation when DO was sufficient.